2016
DOI: 10.1177/2333721416672970
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of a Mobile Health Intervention for Older Adults on Oral Anticoagulation Therapy

Abstract: Background: Oral anticoagulation treatment (OAT) such as warfarin therapy is recommended for older adults with atrial fibrillation, heart failure, or who are at risk for venous thromboembolism. Despite its proven benefits, older adults report both dissatisfaction with OAT and reduced quality of life that can potentially lead to low adherence to OAT and decreased treatment efficacy. Objective: To test the feasibility of Mobile Applications for Seniors to enhance Safe anticoagulation therapy (MASS), a mobile-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(76 citation statements)
references
References 25 publications
2
74
0
Order By: Relevance
“…In line with the above trend, a previous American study developed an mHealth app for older patientson warfarin therapy to promote independence and self-care 26 . That study demonstrated, over a short observation period, a significant enhancement in patients' anticoagulation knowledge, but only using the OAK test.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In line with the above trend, a previous American study developed an mHealth app for older patientson warfarin therapy to promote independence and self-care 26 . That study demonstrated, over a short observation period, a significant enhancement in patients' anticoagulation knowledge, but only using the OAK test.…”
Section: Discussionmentioning
confidence: 84%
“…A previous Chinese study with a larger sample size (N = 110) 44 developed an mApp specifically for patients with a sole warfarin indication (atrial fibrillation only), which in contrast to the previous mApp study 26 , demonstrated significant improvements in all outcomes including knowledge, adherence, anticoagulant satisfaction, and quality of life, besides a reduction in anxiety and depression. However, despite the similarity in the age groups (≥ 65 years) included in both previous mApp studies 26,42 , the larger sample size in the latter study could be a reason for the evident effect of the mApp intervention on PROs. In contrast to both studies, in our study, the age variable was normally distributed, and our patients were relatively younger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data extraction was undertaken using a descriptive‐narrative approach . There were 35 selected articles . Tables were used to collate and summarise the data, and these data were shared within the research team.…”
Section: Methodsmentioning
confidence: 99%